EVIDENCE FOR PLANAR EVENTS IN E+E- ANNIHILATION AT HIGH-ENERGIES - Brandelik, R; Braunschweig, W; Gather, K; Kadansky, V; Lubelsmeyer, K; Mattig, P; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Schultzvondratzig, A; et al. (1979)
Hadron jets produced in e+e- annihilation between 13 GeV and 31.6 GeV in c.m. at PETRA are analyzed. The transverse momentum of the jets is found to increase strongly with c.m. energy. The broadening of the jets is not uniform in azimuthal angle around the quark direction but tends to yield planar events with large and growing transverse momenta in the plane and smaller transverse momenta normal to the plane. The simple qq collinear jet picture is ruled out. The observation of planar events shows that there are three basic particles in the final state. Indeed, several events with three well-separated jets of hadrons are observed at the highest energies. This occurs naturally when the outgoing quark radiates a hard noncollinear gluon, i.e., e+e- → qqg with the quarks and the gluons fragmenting into hadrons with limited transverse momenta. © 1979.